Peran Bantuan Muslim Eropa dalam Meningkatkan Ketahanan Pangan Masyarakat Miskin di Lereng Merapi, Magelang - Abdullah, Muqni Affan (Jurnal Sosial Humaniora Sigli, 2024)
The slopes of Merapi in Magelang, Central Java, are known as an area prone to natural disasters, significantly impacting the community's food security. The high poverty rates and dependence on agriculture make many families vulnerable to food instability. The European Muslim Aid Qurban Program is one of the initiatives to improve food security by distributing qurban meat to the poor in the region. This study aims to evaluate the role of the program in strengthening food security in the Merapi slopes area. The methodology used includes qualitative and quantitative approaches, with data collected through in-depth interviews, field surveys, and secondary data analysis. The research results show that the program has successfully improved the nutritional intake of the community by providing a vital source of animal protein. In addition, the program also contributes to building local capacity by involving the community in the distribution and management of aid. The findings indicate that the program impacts not only the short-term fulfillment of food needs but also contributes to building long-term self-sufficiency and food security. Recommendations from this study include the need to strengthen collaboration between various parties and increase local capacity to ensure program sustainability. The results of this study can serve as a reference for developing similar programs in other areas facing similar food security challenges.